Histoire du politique au Congo-Kinshasa: Les concepts à l’épreuve (1) Mobutu (2) Gauthier de Villers (1) Jean-Pierre Langellier (2) (1) Academia-L’Harmattan, Ottignies, 2016, (2) Perrin, Paris, 2017 - Hendrickx, Colin (Afrika Focus, 2018)
This review article analyses two publications which deal with the history of the independent Democratic Republic of the Congo/Zaire, emphasising the reign of President Mobutu Sese Seko. In comparing the two publications, originating from two decidedly different traditions, the pre- sent article concludes that, twenty years after the fall of the Mobutu regime, there is not (yet) a historiographic consensus on the character of the Mobutu regime. Jean-Pierre Langellier, com- ing from the world of journalism, emphasised in his biography of Mobutu the importance of the President’s friendship ties with the West, and the influence of the Cold War. Conversely, scholar Gauthier de Villers relativised the deterministic character of the Cold War on the regime, as well as the unconditional amical ties of Mobutu with his Western allies. Key words: Congo, DRC, Mobutu, Zaire